Transnational Entrepreneurship as a Win-Win Scenario of International Knowledge Spillover - Veréb, Vanda N. (2018)
This study aims to advance the common domain of knowledge spillovers (KS) and strategic entrepreneurship (SE) by pinpointing further links between these two fields, and by providing a series of real examples of how KS can be strategically applied for the long-term gain of all parties involved in the KS process. Unlike it is assumed as per the traditional view of the KS literature, there is a win-win scenario benefiting both the knowledge generating, sending and the knowledge reaping, receiving economies. As the main conclusion of this analysis, transnational entrepreneurship (TE) is an example of how international KS can be beneficial for both the incumbent and recipient economies. This benefit is derived from the mobile and multiple-embedded nature of transnational entrepreneurs (TEs) and realised through providing economic, cultural, social and institutional assets to both countries.